(untitled) (Ius Novum, 2020)
The article discusses the issues concerning extensive amendments to the provisions of the Criminal Code laid down in the Act of 13 June 2019. It considers the most important solutions introduced to the General part of the Criminal Code in the field of penalties and sentencing. These concern: elimination of the penalty of deprivation of liberty for 25 years from the catalogue of penalties; increasing the maximum limit of the penalty of deprivation of liberty for a period determined by court from 15 years to 30 years; modification of the content of Article 37a CC admitting a possibility of imposing a fine or the penalty of limitation of liberty instead of the penalty of deprivation of liberty; general directives on judicial sentencing decisions and the catalogue of aggravating and extenuating circumstances; and imposition of the penalty of life imprisonment without a possibility of conditional release. The analysis carried out leads to a conclusion that the proposed solutions do not deserve approval.